Community-led development and collective land tenure for environmental justice: the case of the Caño Martín Peña community land trust, Puerto Rico. Issue 1 (31st December 2022) - Veronesi, Mariangela; Algoed, Line; Hernández Torrales, María E.
ABSTRACT: Community-led land ownership can contribute to environmental justice in disaster-prone areas, particularly as it protects vulnerable communities from market-driven displacement often occurring after natural disasters. The article reviews literature linking the climate emergency with disaster resilience and collective land-based models. It brings into focus the case of the Caño Martín Peña communities in San Juan, Puerto Rico, where residents started a Community Land Trust (CLT) in Latin America and the Caribbean, resulting from an extensive process of community participation. We highlight the importance of this case as still one of the only CLT's in the Global South, a mechanism not yet sufficiently understood as a highly developed instrument for secure land tenure and adaptation to climate change in the Global South. We analyse the mechanisms by which the CLT's collective tenure model effectively ensures greater environmental justice – both regarding ongoing flooding issues, and specific extreme natural events such as hurricanes. Collective land ownership allows residents to remain in the area despite forces of gentrification and displacement after disasters induced by global warming. We conclude with a reflection on the need for similar land-based solutions, and summon public authorities to consider these as a route to effective environmental management.